Transformation of Islamic education in the digital age: Challenges and opportunities - Restalia, Winda; Khasanah, Nur (Tadibia Islamika: Journal of Holistic Islamic Education, 2024)
The rapid development of digital technology has driven the transformation of Islamic education, presenting both challenges and opportunities. This study employs a descriptive qualitative approach to explore how technology reshapes teaching and learning processes in Islamic educational institutions, such as madrasahs. By involving key stakeholders—teachers, students, school principals, and parents—selected through purposive sampling, the research captures diverse perspectives on the integration of technology in Islamic education. Data collection methods include semi-structured interviews, participatory observations, and analysis of relevant documents, with thematic analysis used to identify patterns and themes. Findings highlight significant challenges, including the digital divide in underdeveloped regions, limited digital literacy among educators, and curricula that are misaligned with technological advancements. Despite these barriers, technology offers vast opportunities to enhance Islamic education. E-learning platforms and Islamic applications expand access to education globally, fostering inclusivity. Interactive digital content, such as Quran learning apps and educational games, enriches learning experiences, while enabling personalized approaches. Moreover, technology facilitates global collaboration among institutions, promoting resource sharing and curriculum standardization. These findings underscore the importance of addressing digital disparities and equipping educators with the skills needed to harness technology effectively, ensuring that Islamic education thrives in the digital era.